2015
DOI: 10.1007/s11627-015-9706-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro approaches for conservation of Asparagus racemosus Willd.

Abstract: Asparagus racemosus is a commercially important medicinal plant, traditionally used for combating gynecological problems in India. The majority of plants used by the pharmaceutical industry come from wild sources, endangering the natural population of the species. The plants are being overharvested, so this species faces a real danger of becoming vulnerable in its natural habitat. Ex situ conservation using in vitro tools is a possible solution to this problem. Ex situ conservation of plants involving in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
4
10
0
1
Order By: Relevance
“…Number of shoots as well as shoot length decreased as the concentration of BAP decreased/increased beyond 1.0 mg L −1 (Table 1). The multiplication of shoots using BAP has also been reported in T. cordifolia (Raghu et al 2006) as well as in other medicinal plants such as Portulaca oleracea , Asparagus racemosus and Cedrela fissilis (Sharma et al 2011; Thakur et al 2015; Aragão et al 2016) which supports the present results. In contrast to the above results, Faisal and Anis (2003) reported that Kn was optimum for in vitro shooting in Tylophora indica .
Fig.
…”
Section: Resultssupporting
confidence: 89%
“…Number of shoots as well as shoot length decreased as the concentration of BAP decreased/increased beyond 1.0 mg L −1 (Table 1). The multiplication of shoots using BAP has also been reported in T. cordifolia (Raghu et al 2006) as well as in other medicinal plants such as Portulaca oleracea , Asparagus racemosus and Cedrela fissilis (Sharma et al 2011; Thakur et al 2015; Aragão et al 2016) which supports the present results. In contrast to the above results, Faisal and Anis (2003) reported that Kn was optimum for in vitro shooting in Tylophora indica .
Fig.
…”
Section: Resultssupporting
confidence: 89%
“…However, when these osmotic agents were combined with high concentrations of sucrose, the plants after culture for 240 days presented lack of vigor, poor development and irregular growth of the aerial part (Figure 2b) Analogously to the observation in this study, other researchers have observed that the addition of the osmotic agents mannitol or sorbitol together with sucrose was efficient in reducing the growth of other plant species, such as Passiflora gibertii N.E. Brown (Faria et al, 2006), Glycyrrhiza glabra L. (Srivastava et al, 2013) and A. racemosus (Thakur;Tiwari;Jadhav, 2015).…”
Section: Effect Of the Osmotic Agentssupporting
confidence: 86%
“…However, the authors observed a decline in the survival rate and growth of the plants when sorbitol and mannitol were both added to the medium at concentration of 87 mM. Analogously, other authors have reported a phytotoxic effect of these osmotic agents on various plant species, such as A. racemosus Willd (Thakur;Tiwari;Jadhav, 2015) and Piper aduncum L. and Piper hispidinervum C. DC. Scherwinski-Pereira, 2011).…”
Section: Effect Of the Osmotic Agentsmentioning
confidence: 82%
See 1 more Smart Citation
“…In effective reduction in the metabolism of plants in vitro, the cultivation conditions such as temperature, light period, and light intensity may be changed, and so may the components of the cultivation medium (organic and inorganic under different light spectra nutrients, osmotic and growth regulators) during the period of incubation (Thakur et al, 2015;Carvalho et al, 2014;Kaur et al, 2012).…”
Section: Introductionmentioning
confidence: 99%